Catheter-associated bloodstream infection in patients with cancer: comparison of left- and right-sided insertions. (December 2021) - Jones, M.; Okano, S.; Looke, D.; Kennedy, G.; Pavilion, G.; Clouston, J.; Van Kuilenburg, R.; Geary, A.; Joubert, W.; Eastgate, M.; Mollee, P.
Summary: Background: There is limited research on the relationship between side of insertion of central venous catheter (CVAD) and bloodstream infection risk in patients with cancer. Aim: To conduct an exploratory analysis of data from a randomized control trial (RCT) and data from a prospective cohort study to compare infection rates for right- and left-sided insertions. Methods: The study populations were patients aged >14 years with cancer from two tertiary hospitals in Brisbane, Australia. The primary endpoint was catheter-associated bloodstream infection (CABSI) adjudicated by blinded assessors. For the RCT, randomized intention-to-treat comparisons were conducted between left- and right-side allocated insertion for early (≤14 days) and late (>14 days) infection using Cox proportional hazards regression. The RCT data were also combined with cohort study data collected from one of the hospitals prior to the RCT and non-randomized comparisons conducted between left- and right-sided insertions. Findings: In 634 randomly allocated CVADs there were 141 CABSIs. Analysis showed strong evidence of right-side allocated insertions having an increased risk of early infection by 2.5 times (95% confidence interval (CI): 1.3–4.7); however, there was no evidence of increased risk for late infection (hazard ratio: 1.06; 95% CI: 0.71–1.59). Results from analysis of the RCT and cohort study data combined (2786 CVADs and 385 CABSIs) were similar. Conclusion: There appears to be an increased risk of CABSI in patients with cancer for CVAD inserted into the right-side for around two weeks after line insertion. The mechanism underpinning the increased risk is unknown.